Acrania with exencephaly and spinal Myeloschisis in a young pregnant woman from Rural Nepal: A curious case report - Shailendra Katwal, MD; Amrit Bhusal, MBBS; Sushmita Bhandari, MBBS; Kamal Kandel, MBBS; Tek Nath Yogi, MBBS (Radiology Case Reports)
This case report discusses a compelling case involving acrania, exencephaly, and spinal myeloschisis in a 22-year-old pregnant woman from rural Nepal. The delayed diagnosis due to limited healthcare access underscores the importance of early prenatal care and screening. The case sheds light on the complexity of congenital anomalies and their implications. Acrania with exencephaly is a severe cranial neural tube defect that results from the failure of neural tube closure during embryogenesis. Exencephaly on the other hand is the absence of the cranial vault with exposed brain tissue. The study emphasizes the significance of maternal nutrition, folic acid supplementation, and genetic risk assessment in preventing such conditions. This report contributes to raising awareness and improving management strategies for intricate congenital abnormalities, ultimately enhancing maternal and fetal well-being